Optimization of Supervision and Evaluation in Early Childhood Education Management: A Literature Review of the CIPP Model - Nailah Syahlani; Alya Fadiyah Nurul Mashumah; Evelyna Iffah Dinayah; Aprillah Sudirman; Suhardi Suhardi (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study discusses the importance of optimizing the functions of supervision and evaluation in Early Childhood Education (ECE) management. Supervision and evaluation are essential components in ensuring the quality of ECE services in accordance with national education standards. Through a qualitative-descriptive approach, the discussion is directed at the role of internal and external supervision, the implementation of program evaluation, and its impact on improving the quality of ECE institutions. The results of the study indicate that the synergy between supervision and evaluation can enhance the effectiveness of institutional management, the accountability of educators’ performance, and the achievement of learning objectives. Therefore, a continuous, participatory, and data-based supervision and evaluation system is required to support the advancement of ECE institutions in the future.